Sosialisasi Deteksi Dini Speech Delay Di Sekolah Inklusi Kota Surakata - Rizki Husadani; Dian Atnantomi Wiliyanto (CV. Multi Kreasi Media, 2023)
One of the important factors in children's growth and development is the development of language and speech. Developing language skills can help children express feelings, communicate with the person they are talking to, and solve problems. This community service aims to provide insight into the knowledge of accompanying teachers at Surakarta City Inclusion Schools regarding early detection of speech delay in children in elementary schools. The activity was carried out at the UPT Center for Disability Services and Inclusive Education in Surakarta City. The material provided is the definition of speech delay, characteristics and treatment for children who experience speech delay. The stages of community service activities consist of the preparation stage, implementation stage and evaluation stage. The result of this activity is to increase the insight of accompanying teachers in inclusive schools regarding speech delay in elementary school children.